Isolation, characterisation and continuous culture of Lactobacillus spp. and its potential use for lactic acid production from whey (2020)
ABSTRACT : Bioprospecting of microorganisms with the potential of exploiting agro-industrial wastes is an active field of biotechnological research. In this study, we aimed to isolate a microorganism adapted to the dairy matrix with specific characteristics to produce lactic acid from dairy industry wastes, such as whey. Whey was collected from the agricultural region of Antioquia, Colombia, and samples were cultured on Man–Rogosa–Sharpe modified medium using lactose as a source of carbon. The most promising strain isolated was characterised, and its adaptation to whey was determined. A gram-positive Lactobacillus was isolated and named as G1. This strain grows in deproteinised whey with low protein requirements, has a homofermentative metabolism and exhibits high tolerance to low pH (≤5.0). The G1 strain is a promising bacterium for use in lactic acid production from whey, which is an underutilised by-product of the dairy industry.